Pengaruh Teknologi Informasi dan Kompetensi terhadap Kinerja Pegawai dengan Gaya Kepemimpinan sebagai Variabel Intervening pada Kantor Imigrasi Kelas I Khusus TPI Soekarno Hatta - Noptian Hadi Pratama (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to examine the effect of information technology and competence on employee performance with leadership style as an intervening variable at the Class I Special Immigration Office Soekarno Hatta. This research uses a quantitative approach with a sample size of 210 employees. Data collection techniques involved document studies and questionnaires, and data analysis was conducted using SPSS version 25. The results of the study indicate that: (1) Information technology significantly affects employee performance with a t-value of 2.812 > t-table of 1.972 and a significant value of 0.012 < 0.05. (2) Competence also significantly affects employee performance with a t-value of 1.982 > t-table of 1.972 and a significant value of 0.0026 < 0.05. (3) Information technology significantly affects leadership style with a t-value of 2.009 > t-table of 1.972 and a significant value of 0.039 < 0.05. (4) Competence significantly affects leadership style with a t-value of 2.391 > t-table of 1.972 and a significant value of 0.040 < 0.05. (5) Leadership style significantly affects employee performance with a t-value of 2.364 > t-table of 1.972 and a significant value of 0.048 < 0.05. Furthermore, the analysis shows that the direct effect of information technology on employee performance is greater (0.50) than the indirect effect through leadership style (0.08), indicating that leadership style as an intervening variable is not effective. The same applies to competence, with the direct effect (0.95) being greater than the indirect effect (0.152).